Improving Blood Type Checking Readiness in Adolescents Through Teams Games Tournament-Based Education and Video Animation - Rachmania, Diana; Widayati, Dhina (The Indonesian Journal of Health Science, 2023)
Background and Aim:. Every individual is important to know the types of their blood. Most adolesence are still unfamiliar with their blood type because of the lack of readiness of adolescents in examining blood type due to insufficient information. Education with games and video can provide information related to blood type. The aim of this study was determine the effect of education through a combination of Teams Games Tournament (TGT) and video animation on the readiness of blood types examination in adolescents.  Method : Pre-experimental became the design in this study involving 40 respondents through purposive sampling. Readiness of blood types examination variable was measured using a questionnaire. Data  analyzed by Wilcoxon test. Results: before being given an intervention, almost half of adolescents (45%) were not ready to check blood type and after being given an intervention, most (57.5%) were very ready to check blood type.  Conclusion: Education through a combination of TGT and video animation give a good effect on readiness of blood types examination in adolescents. This intervention can affect the readiness of adolescents through increasing knowledge so that they have a positive attitude and become more prepared in carrying out blood group tests. In TGT and animation videos, adolescents will use the five senses more so that it is easier for the brain to understand and generates a stimulus in the form of an attitude of readiness in examining blood type. Education with game and video-based media can be a method of education for adolescents.